Problems and challenges faced by umemployed women in Shoromong Village of Mopani Disrict - Mangena, E D (University of Limpopo, 2014)
Unemployment is a crucial problem in the whole world. There are still a high number of unemployed rural women in the world in general and in South Africa in particular. Rural women are still marginalized and stay in poor conditions because they are unemployed, poor and lack skills required by the market. Black rural women form the majority of illiterates and unemployed in the country and this have a negative impact on the development of the country. This means that rural women stay in conditions of squalor because they are unemployed, poor and lack skills required by the labour market. This study focuses on the problems and challenges faced by unemployed rural women. It was conducted in Shoromong village of Greater Tzaneen Municipality in Mopani District. Unemployed rural women need to be empowered through ABET (Adult Basic Education and Training) programmes to stand up and fight poverty, ill health and other social ills they face. Chapter one outlined the background of the problem of unemployment based on the education in the past (before 1994). I also discussed different types of unemployment, causes and their effects. I formulated the following aim of the study: To investigate the problems and challenges faced by unemployed rural women in Shoromong village. In order to achieve the aim outlined above, I formulated the following main research question: What are the problems and challenges faced by unemployed rural women in Shoromong village? It is the objective of this study to develop a detailed picture of the problems and challenges faced by unemployed rural women in Shoromong village, explore the unemployed rural women’s feelings and attitude about their present situation, to contribute towards the development of a programme that will address problems and challenges faced by unemployed rural women, to contribute towards empowerment of rural women in order to enable them to take their rightful place in society and to bring awareness to the local government about poor living conditions in Shoromong village. Chapter two outlines the theoretical framework of the study. It is based on the readings of the relevant literature and preliminary discussions with the unemployed women of Shoromong village. I have also defined the following concepts: social exclusion, poverty, unemployment and adult education. The following critical factors are discussed: loss of respect and dignity, financial constraints, lack of education and skills and poor living conditions. In chapter three, I described the design of the study. One path of data collection, being fieldwork is the main focus. The fieldwork is divided into phases, namely: Introductory phase, extensive fieldwork phase, and observation. Extensive fieldwork comprises of four stages of interviews. An exploratory design was chosen for this study. An explanation and discussion of the instruments that were utilized to collect data from different role players in various phases of data collection is also given. I further explained how the data that has been collected from various phases was analysed using qualitative data analysis method. Chapter four presents the empirical findings and analysis of the study. I have also outlined the detailed views of interviewees in relation to the critical factors of the study. Results of observations of the study are also given. The results of the study indicate that unemployed women are faced with multiple problems and challenges. Those problems and challenges not only affect them as individuals but also affect their children, spouses/husband, relatives, the community and the whole society. The reality is the burden is on the individual who experience unemployment from day to day. Chapter five is the final chapter of my study. It presents the final conclusion and recommendations of the study. It also provides suggestions of what can bring solutions to problems and challenges of unemployed rural women in Shoromong village. This chapter mentioned areas that need to be further researched as ABET field seems to be under- researched. The chapter concludes by discussing “reflections”. It is a section that is about my learning experiences and difficulties that I encountered during the process of this research.
Thesis (M.Ed. (Community and Continuing Education)) --University of Limpopo
Keywords: Unemployed rural women; poverty; Rural women in development - South Africa; Women farmers